Computational modelling and advanced simulations - Murin, Justin; Kompis, Vladimir; Kutis, Vladimir; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This book contains selected, extended papers presented at the thematic ECCOMAS conference on Computational Modelling and Advanced Simulations (CMAS2009) held in Bratislava, Slovakia, June 30-July 3, 2009. Modelling and simulation of engineering problems play a very important role in the classic and new composite material sciences, and in design and computational prototyping of modern and advanced technologic parts and systems. According to this, the existing numerical methods have been improved and new numerical methods have been established for modelling and simulation of more and more complex and complicated engineering problems. The present book should contribute to the effort to make modelling and simulation more effective and accurate.
This book gathers extended papers presented in the thematic ECCOMAS conference on Computational Modelling and Advanced Simulations (CMAS2009) held in Bratislava, Slovakia, June 30 July 3, 2009. Covers recent results in computational modeling and simulations.
Electronic reproduction.
Keywords: Simulation methods; Electronic books